2006
DOI: 10.3121/cmr.4.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Imbalanced Distribution of Plasmodium falciparum EBA-175 Genotypes Related to Clinical Status in Children from Bakoumba, Gabon

Abstract: Objective: The erythrocyte binding antigen 175 kDa (EBA-175) of Plasmodium falciparum is one of the major ligands for red blood cell invasion by merozoites. EBA-175 is a dimorphic antigen but the role that dimorphism plays in host parasite interaction is not fully understood. In this study, we sought to determine the distribution of EBA-175 genotypes and its pathogenetic influence. Methods:The nested polymerase chain reaction was used to determine the genotypes of P. falciparum isolates from asymptomatic and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
17
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 26 publications
(31 reference statements)
7
17
1
1
Order By: Relevance
“…This result is therefore consistent with our previously reported data. 30 Overall, our study demonstrated the predominance of the allelic family K1 of MSP-1 locus clearly, confirming data reported elsewhere. 31,32 However, no significant association was found between the occurrence of the K1 genotype and severe malaria; K1 was observed in 82% and 90% PRBC from individuals with severe and uncomplicated malaria, respectively.…”
Section: Discussionsupporting
confidence: 81%
“…This result is therefore consistent with our previously reported data. 30 Overall, our study demonstrated the predominance of the allelic family K1 of MSP-1 locus clearly, confirming data reported elsewhere. 31,32 However, no significant association was found between the occurrence of the K1 genotype and severe malaria; K1 was observed in 82% and 90% PRBC from individuals with severe and uncomplicated malaria, respectively.…”
Section: Discussionsupporting
confidence: 81%
“…Similarly, in Bakoumba, Gabon, the F-fragment was more prevalent in children [19]. Similar frequencies were also described in Nigeria, The Gambia, Gabon, and South Africa [20].…”
Section: Discussionsupporting
confidence: 74%
“…Block 2 of merozoite surface protein (MSP)-1, block 3 of MSP-2, and erythrocyte binding antigen (EBA)-175 were amplified by nested PCR as previously reported. [14][15][16] Briefly, after amplification, 10 µl of each nested PCR product were analyzed by electrophoresis on a 1.5% agarose gel. PCR-positive samples at day 0 and day 14 were processed concomitantly and the bands compared.…”
Section: Dna Amplification For P Falciparum Diagnosismentioning
confidence: 99%